Pemberdayaan KWT Flamboyan Desa Badal Pandean melalui Budidaya Maggot Black Soldier Fly (BSF) untuk Mendukung Ekonomi Sirkular [Empowerment of Flamboyan Women's Farmer Group (KWT) in Badal Pandean Village through Black Soldier Fly (BSF) Maggot Cultivation to Support Circular Economy] - Muarofah, Binti; Mulyati, Tri Ans; Nugraheni, Reny; Pujiono, Fery Eko (Indonesia Berdaya, 2025)
Abstract. Agricultural waste in Badal Pandean Village, which is currently unused, has the potential to cause environmental problems. One strategy to prevent this issue is the cultivation of Black Soldier Fly (BSF) larvae or maggots. Maggot cultivation is known to convert organic waste into valuable and marketable products, thus supporting the implementation of a circular economy. This community service activity aims to increase the knowledge and skills of the Flamboyan Women's Farmer Group (KWT) through maggot cultivation and the use of maggots as fish feed. The activity was carried out in four stages: (a) socialization of maggot cultivation techniques, (b) maggot cultivation training, (c) maggot drying training, and (d) dry maggot packaging training. The results showed a 100% increase in partner knowledge regarding maggot cultivation techniques. After the training, partner skills in maggot cultivation improved to 4.35 (very good). Satisfaction evaluation results also indicated that the Flamboyan KWT group was very satisfied (4.55) with the maggot cultivation community service activity. Abstrak. Limbah pertanian di Desa Badal Pandean yang belum dimanfaatkan saat ini berpotensi menimbulkan permasalahan lingkungan. Salah satu strategi yang dapat digunakan untuk mencegah permasalahan ini adalah melakukan budidaya larva Black Soldier Fly (BSF) atau maggot. Budidaya maggot dikenal dapat mengkonversi sampah organik menjadi produk bernilai guna dan jual sehingga mendukung penerapan ekonomi sirkular. Tujuan kegiatan PKM ini adalah meningkatkan pengetahuan dan keterampilan Kelompok Wanita Tani (KWT) Flamboyan melalui budidaya maggot dan memanfaatkan maggot sebagai pakan ikan. PKM ini dilaksanakan dalam 4 tahap yaitu (a) Sosialisasi teknik budidaya maggot, (b) Pelatihan budidaya maggot, (c) Pelatihan pengeringan maggot, (d) Pelatihan pengemasan maggot kering. Hasil kegiatan PKM menunjukkan adanya peningkatan pengetahuan mitra mengenai teknik budidaya maggot sampai 100%. Setelah kegiatan pelatihan, keterampilan mitra pada budidaya maggot meningkat menjadi 4,35 (sangat baik). Hasil evaluasi kepuasan juga menunjukkan bahwa kelompok KWT Flamboyan sangat puas (4,55) terhadap kegiatan PKM budidaya maggot.